Covid-19 Pandemic: The Intention of Sabah Tamu Business Operators to Stay in The Tamu Business - Jaratin Lily; Sidah Idris; Abdul Rahman Yaakob; Zuraidah Jamrin; Nurfarhana Mohd Saidi (Penerbit UMS, 2021)
This study investigates the tamu business operator’s intention to stay in the current business due to the COVID-19 pandemic in the West Coast of Sabah. Overall, the mean score for the intention to stay in the tamu business was considered high with 3.95 mean scores. Using the ANOVA test, the findings indicated that only the length of years involved in tamu business showed a significant mean difference among the respondents. The post hoc test showed that those in the tamu business for more than six years have a higher statistically significant mean difference than those in the tamu business for 3 – 5 years, and two years and below. There was no statistically significant mean difference between those in the tamu business for two years and below and 3 – 5 years. The findings implied that most tamu operators relied on tamu as their primary business platform, especially those who have been operating their tamu business for a longer period. It might be difficult for them to leave their current business to venture into a new business that they are not familiar with. Therefore, the relevant authorities should provide appropriate supports to these affected tamu business operators.